(untitled) (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY Previous studies have suggested that the surgeon’s experience in breast cancer surgery may affect patient survival. In this registry-based retrospective cohort study, we examined whether quality of care could partly explain this association. METHODS All invasive breast cancers operated on in the private sector between 2000 and 2009 were identified in the Geneva Cancer Registry and followed up for 5 years. Surgeons were classified according to their experience into three categories: ≤5, 6–10, >10 breast cancer operations performed per year. We extracted patient and tumour characteristics. Quality of care was scored as the proportion of 11 quality indicators correctly fulfilled for each patient. Breast cancer-specific mortality was examined with a Cox model adjusted for variables known to affect survival, surgeon experience, and quality of care. RESULTS A total of 1489 patients were operated on by 88 surgeons; 50 patients (3.4%) died from breast cancer during the 5 years of follow-up. Socioeconomic status and country of birth of the patients, as well as period of diagnosis, differed according to the surgeons’ experience. Quality of care provided improved with surgeon’s experience. Surgeons performing >10 operations/year more frequently assessed histology before surgery, excised sentinel lymph nodes, removed ≥10 lymph nodes, and prescribed adjuvant radiotherapy when indicated. Crude breast cancer-specific mortality was lower in patients treated by surgeons performing >10 compared with ≤5 operations/year (hazard ratio [HR] 0.34, 95% confidence interval [CI] 0.17–0.67; p = 0.002). The strength of the association decreased after adjustment for patient and tumour characteristics (HR 0.45, 95% CI 0.21–0.94; p = 0.034) and decreased further after adjustment for quality of care (HR 0.51, 95% CI 0.24–1.08, p = 0.078). CONCLUSIONS The association between surgeon’s experience and 5-year breast cancer survival is at least partly explained by quality of care, patient and tumour characteristics. Further investigations on the impact of other quality indicators such as multidisciplinary networks are needed.